Quadrature Operating Point Stabilizing Technique for Fiber-Optic Fabry-Perot Sensors Using Vernier-Tuned Distributed Bragg Reflectors Laser - Li, Ang; Jing, Zhenguo; Liu, Yueying; Liu, Qiang; Huang, Zhiyuan; Cheung, Yang; Zhang, Yang; Han, Ming; Peng, Wei (IEEE sensors journal, 2021)
Drift of Quadrature operating point (Q-point) due to variations in ambient temperature restricts the demodulation accuracy of fiber-optic extrinsic Fabry-Perot interferometer (EFPI) sensors. To overcome this challenge, in this paper, we propose and demonstrate a self-stabilizing Q-point system based on Vernier-tuned distributed Bragg reflectors (VT-DBR) laser, the laser wavelength is locked to a point with the maximum slope on the interference spectrum of fiber-optic EFPI sensor. Taking advantage of large-tuning range (40nm) and fast wavelength switching capability (<20ns), we develop a robust EFPI acoustic sensor system with stable Q-point operation. When the EFPI sensor is subject to ambient temperature variations, we use an FPGA to implement the fast laser wavelength switching of the laser and automatic Q-point locking that ensure Q-point stability. The operating point drift from Q-point is obtained by dc voltage output changes. Experimental results indicate that stabilizing Q-point of the EFPI sensor is effectively realized during the temperature changes between 27-32°C. Without the stabilization method, the deviation is up to 85.5% of dc voltage output at operating point from Q-point value. With the stabilization method, the deviation is less than 0.68%. This self-stabilizing Q-point method based on VT-DBR laser has a strong ability to resist ambient temperature variations, and provides a novel solution to Q-point drift of fiber-optic EFPI sensors.